Baitul Maal Hidayatullah: Are direct marketing and indirect marketing the right strategies for institutions to expand market share? - Sarif, Reza (Maliki Interdisciplinary Journal, 2025)
Baitul Maal Hidayatullah has successfully achieved a brilliant achievement by winning a silver medal as the best national zakat forum. This achievement was achieved thanks to Baitul Maal Hidayatullah’s commitment and dedication in managing zakat in a transparent, accountable, and professional manner. The brilliant achievements achieved by Baitul Maal Hidayatullah (BMH) cannot be separated from the various strategies carried out by BMH. One of the divisions that has a vital role in the development of BMH is the marketing division. So this study aims to analyze more deeply the strategies carried out by the institution in expanding its market reach. The method used in this study is a descriptive qualitative approach through direct observation and interviews. The results of the study show that their marketing division utilizes a combination of direct and indirect marketing strategies to maximize marketing effectiveness.